Consumption Patterns and Perception on Intake of Drinking Water in Klang Valley, Malaysia - Azlan, A.; Khoo, H.E.; Idris, M.A.; Amin, I.; Razman, M.R. (Pakistan Journal of Nutrition, 2012)
This study aims to report on drinking water consumption patterns and perception on usage of drinking water available in Klang Valley, Malaysia. A total of 225 adults aged 21-65 completed the questionnaire which consists of three sections. Socio-demographic data, drinking water consumption patterns were determined. Perceptions were based on the quality and price as well as reasons for intake of tap, bottled drinking water and bottled mineral water. About 79% of the subjects drank 5 to 12 glasses of water a day. Among the subjects, 73%, 14.8% and 11.9% consumed tap water, bottled mineral water and bottled drinking water, respectively. The reasons for consuming bottled water include safety, health, quality and taste. The results also showed that the subjects perceived low to acceptable qualities for tap water, while bottled drinking water and mineral were perceived as having relatively higher quality. Tap water was considered cheap in price by all subjects, while bottled drinking and mineral waters were rated acceptable to high by most subjects. Findings of this study exemplify the importance of consumers’ perception on drinking water as a mean of education and communication on quality of drinking water they consume.